Petasin and isopetasin reduce CGRP release from trigeminal afferents indicating an inhibitory effect on TRPA1 and TRPV1 receptor channels - Kleeberg-Hartmann, Johanna; Vogler, Birgit; Meßlinger, Karl (Journal of Headache and Pain, 2021)
Background: Butterbur root extract with its active ingredients petasin and isopetasin has been used in the prophylactic treatment of migraine for years, while its sites of action are not completely clear. Calcitonin gene-related peptide (CGRP) is known as a biomarker and promoting factor of migraine. We set out to investigate the impact of petasins on the CGRP release from trigeminal afferents induced by activation of the calcium conducting transient receptor potential channels (TRPs) of the subtypes TRPA1 and TRPV1. Methods: We used well-established in vitro preparations, the hemisected rodent skull and dissected trigeminal ganglia, to examine the CGRP release from rat and mouse cranial dura mater and trigeminal ganglion neurons, respectively, after pre-incubation with petasin and isopetasin. Mustard oil and capsaicin were used to stimulate TRPA1 and TRPV1 receptor channels. CGRP concentrations were measured with a CGRP enzyme immunoassay. Results: Pre-incubation with either petasin or isopetasin reduced mustard oil- and capsaicin-evoked CGRP release compared to vehicle in an approximately dose-dependent manner. These results were validated by additional experiments with mice expressing functionally deleted TRPA1 or TRPV1 receptor channels. Conclusions: Earlier findings of TRPA1 receptor channels being involved in the site of action of petasin and isopetasin are confirmed. Furthermore, we suggest an important inhibitory effect on TRPV1 receptor channels and assume a cooperative action between the two TRP receptors. These mechanisms may contribute to the migraine prophylactic effect of petasins.
CRIS-Team Scopus Importer:2021-04-30
Keywords: Butterbur; CGRP; Isopetasin; Migraine; Petasin; TRPA1; TRPV1